Phosphorylation of Histone H2A at Serine 95 Is Essential for Flowering Time and Development in Arabidopsis - Huang, Tongtong; Zhang, Heng; Zhou, Yiming; Su, Yanhua; Zheng, Han; Ding, Yong (Frontiers in Plant Science, 2021)
Phosphorylation of H2A at serine 95 (H2AS95ph) mediated by MLK4 promotes flowering and H2A.Z deposition. However, little is known about MLK1, MLK2, and MLK3 in flowering time. Here, we systemically analyze the functions of MLK family in flowering time and development. Mutation in MLK3, but not MLK1 and MLK2 displayed late-flowering phenotype. Loss of MLK3 function enhanced the late-flowering phenotype of mlk4 mutant, but not reinforced the late-flowering phenotype of mlk1 mlk2 double mutants. MLK3 displayed the kinase acitivity to histone H2A at serine 95 in vitro. The global H2AS95ph levels were reduced in mlk3 mlk4, but not in mlk3 and mlk4 single mutant, and mlk1 mlk2 double mutant; and the H2AS95ph levels in mlk1 mlk3 mlk4 and mlk2 mlk3 mlk4 were similar to those in mlk3 mlk4 double mutant. MLK3 interacted with CCA1, which binds to the promoter of GI. Correspondingly, the transcription levels and H2AS95ph levels of GI were reduced in mlk3 and mlk4 single mutant, and greatly decreased in mlk3 mlk4 double mutant, but not further attenuated in mlk1 mlk3 mlk4 and mlk2 mlk3 mlk4 triple mutant. Together, our results suggested that H2AS95ph deposition mediated by MLK3 and MLK4 is essential for flowering time in Arabidopsis.